Agroforestry as a sustainable land use option to reduce wildfires risk in European Mediterranean areas - Damianidis, Christos; Santiago-Freijanes, Jose Javier; den Herder, Michael; Burgess, Paul J.; Mosquera-Losada, María Rosa; Graves, Anil; Papadopoulos, Andreas; Pisanelli, Andrea; Camilli, Francesca; Rois-Díaz, Mercedes; Kay, Sonja; Palma, João H. N.; et al. (Springer, 2020)
Wildfires have always been an integral part of the ecology of many terrestrial ecosystems, but their frequency is increasing in many parts of the world. Wildfires were once a natural phenomenon, but after humans learned to control fire, it has been used as a management tool to increase soil fertility, to regenerate natural vegetation for grazing and to control competing vegetation. However, currently uncontrolled wildfires threaten not only natural vegetation, landscape biodiversity, communities and economies, but they also release large amounts of carbon dioxide, thus contributing to global temperature increase. Higher temperatures and drier summers have increased the risk of wildfires in biodiversity rich areas of European Mediterranean countries and have resulted in human casualties. The aim of this article is to investigate whether agroforestry, the practice of integrating woody vegetation and agricultural crops and/or livestock, could be a management tool to reduce wildfires in European Mediterranean countries. Fire events from 2008 to 2017 and data of land cover and land use were spatially correlated. Results indicated that agroforestry areas had fewer wildfire incidents than forests, shrublands or grasslands, providing evidence of the potential of agroforestry to reduce fire risk and protect ecosystems.
Keywords: Land uses; Management; Ecosystems; Climate change; Vegetation types